The relationship between core self-assessment and organizational citizenship behavior motivations with organizational citizenship behavior of schools - کریم سواری (Allameh Tabataba'i University Press, 2015)
This study aimed to determine the relationship between core self-assessment and organizational citizenship behavior motivations with organizational citizenship behavior of schools administrators was conducted in three grades of Behbehan city. Therefore, from all schools administrator of three grades in Behbehan city,113 persons were selected by using simple random sampling.To collect data, core self-assessment questionnaire, organizational citizenship behavior motivations and organizational citizenship behavior questionnaires were used. Research method is correlation. Data analysis was performed by Pearson correlation coefficient and multiple regression. The results showed that the core self-assessment (self-esteem, self-efficacy, the inhibition and nervousness station) with organizational citizenship behavior had significant and positive relationships, and from mentioned variables, self-esteem and nervousness had most role in explaining the organizational citizenship behaviors of administrators , also organizational citizenship behavior motivations ( interest in the organization motivation, community values motivation and removal management motivation ) with organizational citizenship behavior had significant and positive relationship, and from mentioned variables interest in the organization motivation and removal management motivation have played most role in explaining the organizational citizenship behaviors of administrators.